Characterization of the aroma and flavor profiles of guava fruit (Psidium guajava) during developing by HS-SPME-GC/MS and RNA sequencing - Jie Zhang; Yi Zhang; Shuaiyu Zou; Endian Yang; Ziyi Lei; Tingting Xu; Chen Feng (Food Chemistry: Molecular Sciences)
The flavor of guava, an important tropical fruit, is influenced by secondary metabolites. However, the mechanisms and processes underlying flavor formation in guava remain unclear. In this study, dynamic changes in volatile organic compounds (VOCs), sugars, and organic acids in guava peel and flesh across different developmental stages were investigated using headspace solid-phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC–MS) and high-performance liquid chromatography (HPLC). Here, we identified 90 VOCs, three sugars and eight organic acids. The dynamics of VOCs differ between the flesh and peel. The early developmental stages are more critical in influencing the variation of VOCs in the flesh, while VOC changes in peel occur more progressively across the developmental stages. By integrating transcriptomic and metabolomic analyses, we identified several key genes involved in VOC, sugar, and acid metabolism. This is the first study to describe the expression patterns of these genes throughout guava development, providing new insights into guava flavor development.